2018
DOI: 10.1039/c7dt03699j
|View full text |Cite
|
Sign up to set email alerts
|

In situsynthesis of magnesium hydroxides modified with tripodal ligands in an organic medium

Abstract: Layered magnesium hydroxides modified organically with tris(hydroxymethyl)aminomethane (Tris-NH) were directly synthesized from magnesium chloride dissolved in a polar organic solvent, like dimethyl sulfoxide (DMSO), containing a small amount of water. Tris-NH acted as a base for precipitating magnesium hydroxides as well as an organic modifier. In contrast to the case of an aqueous solution, the use of organic solvents substantially increased the degree of modification of layered magnesium hydroxides with Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…20 This implies that some of the tripodal ligands are bonded to the layer with bidentate linkages. 21 The particle size is similar to that of CoAl_Tris_inter(HT) (Figure 4c). Consequently, interlayer-modified LDHNPs were synthesized using Co 2+ or Ni 2+ as a divalent cation of LDHs.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…20 This implies that some of the tripodal ligands are bonded to the layer with bidentate linkages. 21 The particle size is similar to that of CoAl_Tris_inter(HT) (Figure 4c). Consequently, interlayer-modified LDHNPs were synthesized using Co 2+ or Ni 2+ as a divalent cation of LDHs.…”
Section: Resultssupporting
confidence: 61%
“…We have previously reported that suppression of the hydrolysis is important for the formation of hybrid metal hydroxides whose interlayer surfaces are modified with tripodal ligands, from the study on the synthesis of hybrid metal hydroxides in organic media. 21 It is reasonable to apply this hypothesis also for synthesizing interlayer-modified LDHNPs, with certain modifications. The major difference between hybrid metal hydroxides and interlayer-modified LDHNPs is the layer charge; that is, metal hydroxides and LDHNPs consist of neutral and positively charged brucite-type layers, respectively.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The SEM images of Ni–OMe reveal that Ni–OMe is the dense aggregate (Figure S4a) composed of nanoparticles of size 10–20 nm (Figure S4b). The XRD pattern of Ni–OMe shows broad diffraction peaks characteristic of interlayer-modified brucite-type metal hydroxides with small crystallites (Figure b). ,, The peak at d = 0.84 nm can be assigned to diffraction from the basal plane. The expanded basal spacing compared to the thickness of one Ni­(OH) 2 layer ( d 001 = 0.46 nm for β-Ni­(OH) 2 , JCPDS #14-0117) indicates that methoxy groups are immobilized on the surface of the stacked layers.…”
Section: Resultsmentioning
confidence: 99%
“…In order to overcome this issue, we propose the use of organic ligands forming mono or bidentate alkoxy bonds, which are susceptible to hydrolysis, as removable surface modifiers. Our previous study has shown that the use of nonaqueous solvents is effective for the modification of metal hydroxides with alkoxy groups, which are hydrolyzed in aqueous solvents . Therefore, nonmodified nickel hydroxide nanosheets can be prepared by the preparation of hybrid layered nickel hydroxides modified with mono or bidentate alkoxy bonds in an organic solvent and the subsequent hydrolysis of surface modifiers after exfoliation.…”
Section: Introductionmentioning
confidence: 99%